Comparing dual oral agents plus insulin vs. Triple oral agents in uncontrolled type II diabetes: A pilot study. - Nadia Gul; Inayat Ur Rehman; Yasar Shah; Arbab Muhammad Ali; Zahid Ali; Omer Shehzad; Khang Wen Goh; Long Chiau Ming; Amal K Suleiman (PLoS ONE)
Introduction Type II Diabetes mellitus (T2DM) patients often do not achieve glycemic control with oral hypoglycemic agents (OHAs). There are two main approaches to address this challenge: transitioning to a triple OHA regimen, or adding Insulin to the existing dual OHA regimen. Aim This study aimed to compare the efficacy of adding Insulin to dual OHAs (Sitagliptin + Metformin) against adding a third OHA to Sitagliptin + Metformin in achieving glycemic control among patients with uncontrolled T2DM. Method A pre-post study was conducted between 21 September 2023 and 21 December 2023 at Services Hospital Peshawar, Pakistan. Patients with uncontrolled T2DM with >7% HbA1c were divided into group 1 (Sitagliptin + Metformin plus a third OHA), and group 2 (Sitagliptin + Metformin plus pre-mixed Insulin 70/30). Glycemic control based on HbA1c values, fasting and random blood sugar levels, lipid profile, and body weight were evaluated after 3 months of therapy. The pre- and post- effect was compared by using a paired t-test. Results The study included n = 80 patients with T2DM. Between groups 1 and 2, no significant difference was found in HbA1c values (9.1 vs. 9, with p = 0.724). However, BMI, cholesterol, and LDL significantly decreased in group 1 compared to group 2 (p<0.001 vs. p = 0.131, p = 0.023 vs. p = 0.896, and p = 0.003 vs. p = 0.395, respectively). Additionally, the incidence of hypoglycemic episodes was significantly lower in group 1 (7.5%) than in group 2 (47.5%, p = 0.004). No significant difference was observed between the triple OHA and dual OHA plus Insulin regimens in achieving glycemic control. Conclusion The triple OHA regimen improved BMI, cholesterol, and LDL levels, and reduced hypoglycemic episodes more effectively than dual OHA plus Insulin, despite similar HbA1c outcomes, suggesting it may be preferable for uncontrolled T2DM.